Mathematics teachers' views on distance education and their beliefs about integrating computer technology in mathematics courses - Mesut Bütün; Fatih Karakuş (Journal of Pedagogical Research, 2021)
This study examines mathematics teachers' views on distance education and their beliefs about integrating computer technology in mathematics courses in terms of their gender, years of teaching experience and grade level taught. Moreover, this study investigates whether beliefs about integrating computer technology in mathematics courses can be a predictor of teachers' views on distance education. Data were collected from the 133 middle school and secondary school mathematics teachers at the end of the fall term of the 2020-2021 academic year in Sivas, Turkey. Data collection tools were Distance Education Perceptions of Teachers Scale (DEPT) and Belief Scale towards Using Computer Technology in Mathematics Instruction (BSMI). Both descriptive and inferential statistics were used to analyze the data. The results showed that mathematics teachers' general DEPT scores were at a moderate level. And there was no significant difference in teachers' DEPT scores regarding their gender, grade level taught and experience. The results also revealed that teachers' BSMI scores were mostly at a high level and there were no differences in their BSMI scores with respect to their gender, grade level taught and experience regarding. Moreover, these beliefs have been found to have an effect on their views on distance education; the BSMI variable explains 13% of teachers' DEPT.